Revisiting Leadership in Public Finance: Evidence on Non-Tax Revenue Receivables Management Quality in Indonesia - Wibowo, Puji; Firmansyah, Amrie; Suhendra, Maman; Subardianta, Ari Untung; Krisnandono, Diananto (Accounting Analysis Journal, 2025)
Purpose: The study examines factors affecting the quality of Non-Tax State Revenue (NTR) receivable management, focusing on human resource competence, internal control, and servant leadership. Despite NTR growth, audit findings reveal ongoing weaknesses, particularly in receivable collection effectiveness. Method: The study employs a quantitative survey approach with 151 respondents across ministries, comprising civil servants managing NTR at State Ministries and Institutions. Data is analyzed using structural equation modeling (SEM) with partial least squares (PLS) software to examine the relationships between key variables. Findings: The results show that human resource competence and internal control positively influence the quality of NTR receivable management. However, servant leadership does not enhance the positive effects of these factors, indicating that leadership style may not be a critical moderating variable in this context. Alternatively, transactional or transformational leadership may be preferrable for NTR receivable management in Indonesian context. Novelty: The research expands the public sector accounting literature by shifting the focus from leadership-driven models to a competency-driven, control-based approach in NTR receivable management. The findings challenge the conventional emphasis on leadership in public finance and suggest that structured policies, internal control mechanisms, and human resource competency are more effective in ensuring financial governance and revenue optimization.